Plant development influences dynamic shifts in the root compartment microbiomes of wild and domesticated finger millet cultivars - Fantaye Ayele Dadi; Saraladevi Muthusamy; Samrat Ghosh; Diriba Muleta; Kassahun Tesfaye; Fassil Assefa; Jie Xu; Farideh Ghadamgahi; Rodomiro Ortiz; Ramesh Raju Vetukuri (BMC Microbiology)
Abstract Background Plant-microbe interactions in the rhizosphere and endosphere are crucial for maintaining plant health and ecosystem dynamics. These interactions are shaped by several factors, including the plant’s developmental stage, domestication, and specific root compartments. Different plant cultivars influence unique microbial communities by secreting root exudates that either support beneficial symbionts or inhibit pathogens. This study examined the microbial community structures in the endosphere and rhizosphere of wild-type finger millet and five domesticated cultivars at two developmental stages. Results Our results revealed that the plant developmental stage, root compartment, and domestication significantly influence the root-associated microbiomes. Interestingly, only about 8% of the core microbiota was consistently shared between the soil and plants, indicating that 92% shifted dynamically depending on plant type and developmental stage. Pseudomonadota, Actinomycedota, and Bacteroidota were the dominant bacterial phyla, while Ascomycota and Basidiomycota were the primary fungal phyla across all samples, displaying distinct abundance patterns. Notably, an increase in Actinomycedota in the endosphere correlated with a reduction in Pseudomonadota. The most significant shifts in microbial community composition occurred in the rhizosphere during the flowering stage, primarily driven by the genus Pseudomonas. These findings demonstrate that plant developmental stages and domestication influence the recruitment of specific microbial taxa to meet the plant’s needs, particularly in various root compartments. This selective recruitment highlights the active role of plants in shaping their microbiomes, providing insights into the potential for manipulating these communities to enhance crop productivity sustainably. Conclusion Our results indicate that both the host developmental stage and domestication significantly influence the assembly and structure of the plant microbiome. Plant root compartments can selectively recruit specific taxa from associated core microbial communities to meet their needs, depending on the plant’s developmental stage and the particular root compartment involved. These findings demonstrate that the deterministic selection pressures exerted by plants during their growth and development greatly affect their microbial communities. This has important implications for developing sustainable farming practices, reducing reliance on chemical fertilizers and pesticides, and enhancing future crop productivity.